The significance of education to the Aymara nation - Alanoca Arocutipa, Vicente; Mamani Luque, Ofelia Marleny; Condori Castillo, Wido Willam (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article deals with the significanceof the education of relevance undertaken by the Aymara nation in the last 100 years of republican life in the Peruvian context. Special attention was given to the department of Puno. For this study, existing historical information was used and it was also possible to identify the processes and spaces where, the still alive, demand for education arose. The ethnographic method was used to describe the historical and outstanding scenarios of this process, such as the parameterized schooling; school nuclei; the Puno-Tambopata project; the experience of Bilingual Intercultural Education, and the struggle for and access to higher education. All these facts marked history.  Our purpose was to visualize the significanceof education for the Aymara nation, from the Peruvian context, in search of a solution to the major social, economic, political, and cultural problems facing the country. The struggle for education of relevance, within the framework of the country's development, was initiated in 1902 by Manuel Z and has not yet ceased. Nowadays, the demand focuses on the creation of the Universidad Nacional Autónoma Aymara, that is, higher education of relevance in line with the changes and the  pluricultural - multilingual trends. Although this may seem incongruous, it is the dream and aspiration of the Aymara people.